EFFECTIVENESS OF BLUE COVARINE IN WHITENING OF TEETH: A SYSTEMATIC REVIEW (International Journal of Food and Nutritional Sciences, 2022)
BACKGROUND:Blue covarine is a new and emerging pigment used in whitening toothpaste. On its use, a thin coat of semi-transparent film is deposited on the surface of the teeth. This layer modifies the interaction of the incident light on the surface of the tooth, causing a shift in the yellow-blue colour axis leading to decreased yellowness and increased blueness, making the teeth look perceptibly whiter.OBJECTIVE:The objective of this systematic review is to prove the effectiveness of blue covarine in the whitening of teeth.